Fish biogeography in the "Lost World" of the Guiana Shield: Phylogeography of the weakly electric knifefish Gymnotus carapo (Teleostei: Gymnotidae). (10th February 2018) - Lehmberg, Emma S.; Elbassiouny, Ahmed A.; Bloom, Devin D.; López‐Fernández, Hernán; Crampton, William G.R.; Lovejoy, Nathan R.
Abstract: Aim: The Guiana Shield region exhibits extraordinary topography that includes sheer, flat‐topped mountains (tepuis) atop an upland platform. Rivers of the eastern Pakaraima Mountains descend to Atlantic coastal lowlands, often traversing spectacular rapids and waterfalls. For fish species distributed in both uplands and lowlands, it is unclear whether these rapids and waterfalls present population or biogeographical boundaries. We sought to test this using the geographically widespread banded‐electric knifefish ( Gymnotus carapo ) as a model. Location: The Guiana Shield region of South America. Methods: We sampled 60 Gymnotus carapo specimens from the Guiana Shield region, and 75 G. carapo and closely related species from other parts of South America. We sequenced the mitochondrial cytochrome b gene and an intron from the nuclear S7 ribosomal protein gene, and used maximum likelihood and Bayesian tree‐building approaches to generate phylogenetic trees of haplotypes. Results: Haplotype sharing is minimal between populations separated by elevational barriers. We found evidence for two main haplotype clades in the Guiana Shield: one distributed in Atlantic coastal regions that includes most lowland samples, and one inland that includes most upland samples. Inland Guiana samples are more closely related to samples from the Amazon basin than to those of Atlantic coastal regions. A single sample from Tafelberg tepui in Suriname was most closely related to the Atlantic coastal lineages. Main conclusions: Riverine barriers that result from steep elevational gradients in the Guiana Shield inhibit gene flow between uplands and lowlands, even for a widely distributed species. Biogeographical relationships of Guiana Shield G. carapo are complex, with most upland lineages showing affinities to the Amazon basin, rather than to nearby lowland drainages of the Atlantic coast.